Image-based adaptive optics for two-photon microscopy. - Débarre, D; Botcherby, E; Watanabe, T; Srinivas, S; Booth, M; Wilson, T (2009)
We demonstrate wavefront sensorless aberration correction in a two-photon excited fluorescence microscope. Using analysis of the image-formation process, we have developed an optimized correction scheme permitting image-quality improvement with minimal additional exposure of the sample. We show that, as a result, our correction process induces little photobleaching and significantly improves the quality of images of biological samples. In particular, increased visibility of small structures is demonstrated. Finally, we illustrate the use of this technique on various fresh and fixed biological tissues.